Development of a Model Mobile Training Management to Improve Quality Outcome of Education and Training for Coastal Communities in East Java - Anak Agung Ngurah Ade Dwi Putra Yuda; Bambang Suratman; Yatim Riyanto (Indonesia Approach Education, 2021)
This research aims to analyze the practicality of developing a mobile training management model to improve the quality of education and training outcomes for coastal communities in East Java at the Surabaya Shipping Polytechnic. This study uses a qualitative approach that is based on the philosophy of positivism. Research subjects are employees who are involved in the implementation of the training, management experts who are masters in their fields and understand the training activities. This development research uses three kinds of data collection methods, namely observation, interviews, and documentation. The research procedure used development adapted from Borg and Gall. Based on the research analysis, it can be concluded that the development of a mobile training management model to improve the quality of the training results is practical. The practicality of the mobile training model is shown by a very good category of assessment responses by expert users of mobile training management model development product users and the audience. Then results of the product trial to the community received some input and suggestions on some of the findings of obstacles to the application of the model. This research implies that it can be used as a guideline by coastal communities to improve the quality of safety during shipping